Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1051/0004-6361:20041903
|View full text |Cite
|
Sign up to set email alerts
|

AGN variability time scales and the discrete-event model

Abstract: We analyse the ultraviolet variability time scales in a sample of 15 type 1 Active Galactic Nuclei (AGN) observed by IUE. Using a structure function analysis, we demonstrate the existence in most objects of a maximum variability time scale of the order of 0.02-1.00 year. We do not find any significant dependence of these maximum variability time scales on the wavelength, but we observe a weak correlation with the average luminosity of the objects. We also observe in several objects the existence of long-term v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Collier & Peterson (2001) studied 4 of the objects presented here and found a τ max significantly smaller in all cases for the optical and UV. The same applies for the AGN variability study performed by Favre et al (2005) using UV data, including 7 of the objects studied here. On the contrary, de Vries et al (2005) do not find a turn-over in optical lightcurves up to τ max ∼ 40 yr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collier & Peterson (2001) studied 4 of the objects presented here and found a τ max significantly smaller in all cases for the optical and UV. The same applies for the AGN variability study performed by Favre et al (2005) using UV data, including 7 of the objects studied here. On the contrary, de Vries et al (2005) do not find a turn-over in optical lightcurves up to τ max ∼ 40 yr.…”
Section: Discussionmentioning
confidence: 99%
“…Applications to other data sets have been shown, e.g. by Hughes et al (1992), Paltani (1999), de Vries (2005, and Favre et al (2005). The structure function is a useful and simple to use tool in order to find characteristic time scales for the variations in a source.…”
Section: Structure Functionmentioning
confidence: 99%
“…Two possibilities are envisaged: either the variability process does not follow a Poisson distribution or the individual events are not identical, with the latter hypothesis being more plausible. Indeed, Favre et al (2005) found a lack of correlation between event rate and object luminosity, suggesting that a larger total luminosity cannot only be explained by a greater number of identical events. This implies that the event energy cannot be the same for all events.…”
Section: Optical/uv Variabilitymentioning
confidence: 99%
“…Collier & Peterson (2001) derived a characteristic optical/UV time scale of ∼5-100 days in a sample of 10 AGNs, performing a structure function analysis. Studying the variability time scales in the framework of discrete-event models, Favre et al (2005) showed a lack of (strong) dependence of the event duration on the source luminosity, hence on central mass. In their sample, the average luminosity of the sources covered four orders of magnitude, while the event duration varied by only two orders of magnitude.…”
Section: Optical/uv Variabilitymentioning
confidence: 99%
“…In this case, the structure function is to be preferred over power spectral density (PSD) analysis (e.g. Hughes et al 1992;Collier & Peterson 2001;Favre et al 2005). The SF was first introduced by Simonetti et al (1985), and has since been used in various bands, including radio (e.g.…”
Section: The Structure Functionmentioning
confidence: 99%